Development of an Ethnic-Math HOTS-Based Assessment Instrument to Measure Students' Numerical Literacy - Andi Asma (Yayasan Keluarga Guru Mandiri, 2023)
This study aims to develop an Ethnic Math HOTS Assessment Instrument to measure the numerical literacy of the 8th-grade students in Manado. The research used the Research and Development method. This research and development included potential and problems, information gathering, product design, design validation, design revision, product trial, and product revision. Data analysis was used to collect qualitative and quantitative data from experts' assessments, material experts, and media experts. The result of testing expert eligibility assessment was 81%, the material expert was 80%, media experts was 88%, the small-scale trial was valid with r count r table 0.361 and reliable with a reliability coefficient of 1.653, and practical test results where the attractiveness was 31%, the use process was 20%, the convenience was 20%, the time was 9%, and the evaluation was 20%, and the large-scale trial was also valid and reliable. These results can provide information about students' capacities in numerical literacy. The HOTS ethnic math assessment instrument can be used as an assessment tool in the learning process.